Anti-HCV Tannins From Plants Traditionally Used in West Africa and Extracted With Green Solvents - Bamba, Moussa; Bordage, Simon; Sahuc, Marie-Emmanuelle; Moureu, Sophie; Samaillie, Jennifer; Roumy, Vincent; Vauchel, Peggy; Dimitrov, Krasimir; Rouillé, Yves; Dubuisson, Jean; Tra Bi, Fézan Honora; Séron, Karin; et al. (Frontiers in Pharmacology, 2022)
Millions of people are still infected with hepatitis C virus (HCV) nowadays. Although recent antivirals targeting HCV proteins are very efficient, they are not affordable for many people infected with this virus. Therefore, new and more accessible treatments are needed. Several Ivorian medicinal plants are traditionally used to treat “yellow malaria”, a nosological category including illness characterized by symptomatic jaundice such as hepatitis. Therefore, some of these plants might be active against HCV. An ethnobotanical survey in Côte d’Ivoire allowed us to select such medicinal plants. Those were first extracted with methanol and tested for their anti-HCV activity. The most active ones were further studied to specify their IC50 and to evaluate their toxicity in vitro. Greener solvents were tested to obtain extracts with similar activities. Following a phytochemical screening, tannins of the most active plants were removed before re-testing on HCV. Some of these tannins were identified by UPLC-MS and pure molecules were tested against HCV. Out of the fifteen Ivorian medicinal plants selected for their putative antiviral activities, Carapa procera DC. and Pericopsis laxiflora (Benth. ex Baker) Meeuwen were the most active against HCV (IC50: 0.71 and 0.23 μg/ml respectively) and not toxic for hepatic cells. Their crude extracts were rich in polyphenols, including tannins such as procyanidins A2 which is active against HCV. The same extracts without tannin lost their anti-HCV activity. Replacing methanol by hydro-ethanolic solvent led to tannins-rich extracts with similar antiviral activities, and higher than that of aqueous extracts.